Electrical Properties of Poly (Ethylene Oxide) polymer Doped by MnCl2 - Salih, A. A.; Ramadin, Y.; Zihlif, A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The electrical properties of Poly (ethylene oxide)-MnCl2 Composites were studied by using the impedance technique. The study was carried out as a function of frequency in the range from 10 Hz to 13 MHz and MnCl2 salt concentration ranged from 0% to 20% by weight. It was found that the dielectric constants and the dielectric loss of the prepared films increase with the increase of the MnCl2 concentration; The A.C. conductivity increases with the increase of the applied frequency, and the MnCl2 content in the composite membrane. Relaxation processes were observed to take place for composites which have a high salt concentration. The observed relaxation and polarization effects of the composite are mainly attributed to the dielectric behaviour of the MnCl2 filler and polarity of the polymer PEO. However, the results were explained on the basis of the interfacial (space charge) polarization dipolar polarization and the decrease of the hundrance of the polymer matrix with the ionic mobility and impurities in the composite.